2021
DOI: 10.1155/2021/7887213
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Challenges of an Abdominal Pregnancy in the Second Trimester

Abstract: Abdominal pregnancies are a rare form of ectopic pregnancy, which presents a significant risk of maternal morbidity and mortality. We describe an unusual case of a late diagnosis of an abdominal pregnancy in the second trimester, which due to diagnostic challenges, was not detected on 1st trimester and subsequent antenatal ultrasound scans (USS). The abdominal pregnancy was later diagnosed at the repeat anomaly scan and confirmed with a pelvic MRI. This case of abdominal pregnancy is unique when compared to ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Secondary intra-abdominal pregnancy is more common and is often the result of peritoneal implantation following rupture of the fallopian tube, ovary, or intrauterine pregnancy. [5,7] In the present case, the patient uterus was intact during the operation, the left adnexa appeared normal, and the normal anatomical structure of the right adnexa was unclear. The postoperative pathology showed that the placental fetal surface had the umbrella end of the fallopian tube, which was considered to happen after the fallopian tube rupture.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Secondary intra-abdominal pregnancy is more common and is often the result of peritoneal implantation following rupture of the fallopian tube, ovary, or intrauterine pregnancy. [5,7] In the present case, the patient uterus was intact during the operation, the left adnexa appeared normal, and the normal anatomical structure of the right adnexa was unclear. The postoperative pathology showed that the placental fetal surface had the umbrella end of the fallopian tube, which was considered to happen after the fallopian tube rupture.…”
Section: Discussionmentioning
confidence: 62%
“…It is an extremely rare type of ectopic pregnancy, with an incidence rate of 1:10000 to 1:30000, accounting for 0.6% of all ectopic pregnancies. [ 2 , 5 ] Most abdominal pregnancies originate from ruptured tubal pregnancies, and in some cases, the implantation occurs directly on the uterine serosa, omentum, intestine, and mesentery, thereby increasing the risk of fatal intra-abdominal hemorrhage. [ 6 ] Reportedly, the maternal mortality rate of abdominal pregnancy is approximately 7.7 times that of tubal pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce this limitation, use of criteria such as; (1) demonstration of a foetus in a gestational sac outside the uterus; (2) failure to visualize the uterine wall between the foetus and urinary bladder; (3) proximity between the foetus and the anterior abdominal wall; and (4) localization of the placenta outside the confines of the uterine cavity has been proposed [ 16 ]. More advanced diagnostic modalities such as magnetic resonance imaging provides superior outcome compared to ultrasound scans [ 17 ] but are rarely available in resource limited-setting.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of late abdominal pregnancy was missed. The diagnosis of abdominal pregnancy in the second and third trimester is difficult and can be missed up to 50% of the time, despite regular antenatal care and imaging [11,17]. Chen et al published a case report of abdominal pregnancy and review of 17 other cases, and reported that only 5 out of 17 cases were diagnosed before surgery [9].…”
Section: Discussionmentioning
confidence: 99%